Metabolic Regulation of Macrophage Activation - Ourania Kolliniati; Eleftheria Ieronymaki; Eleni Vergadi; Christos Tsatsanis (Karger Publishers, 2021)
Macrophages, the central mediators of innate immune responses, being in the first-line of defense, they have to readily respond to pathogenic or tissue damage signals to initiate the inflammatory cascade. Such rapid responses require energy to support orchestrated production of pro-inflammatory mediators and activation of phagocytosis. Being a cell type that is present in diverse environments and conditions, macrophages have to adapt to different nutritional resources. Thus, macrophages have developed plasticity and are capable of utilizing energy at both normoxic and hypoxic conditions and in the presence of varying concentrations of glucose or other nutrients. Such adaptation is reflected on changes in signaling pathways that modulate responses, accounting for the different activation phenotypes observed. Macrophage metabolism has been tightly associated with distinct activation phenotypes within the range of M1-like and M2-like types. In the context of diseases, systemic changes also affect macrophage metabolism, as in diabetes and insulin resistance, which results in altered metabolism and distinct activation phenotypes in the adipose tissue or in the periphery. In the context of solid tumors, tumor-associated macrophages adapt in the hypoxic environment, which results in metabolic changes that are reflected on an activation phenotype that supports tumor growth. Coordination of environmental and pathogenic signals determines macrophage metabolism, which in turn shapes the type and magnitude of the response. Therefore, modulating macrophage metabolism provides a potential therapeutic approach for inflammatory diseases and cancer.